THE EFFECT OF QUANTUM LEARNING METHOD IN IMPROVING WRITING ABILITY IN DESCRIPTIVE TEXT AT EIGHT GRADE OF SMP NEGERI 27 MEDAN - Sondang Sinaga; Fenty Debora Napitupulu; Sahat Taruli Siahaan (Jurnal Scientia, 2023)
The study's goal is to determine how the Dictation Method affects the writing abilities of students at SMP Negeri 27 in Medan. This study's research methodology was an experimental quantitative design. Students in grades VIII from SMP Negeri 27 in Medan, make up population of this study. The research's sample consists the VIII 5 and 6 classes, which were chosen at random. As the control group, the second group consists of 42 pupils. Pre-test and post-test are the two separate tests. The t-test procedure was used to examine the data in order to determine whether the Quantum method has an impact on students' writing abilities. The analysis's findings indicate that the t-test was and t-table was 1.7011 (p-0,05), it was concluded that the t-observed > t-table (8, 1710>1,7011). The higher score was found by applying Quantum technique. It means that the application of Quantum technique affected significantly on the skill of writing descriptive text. It means that the alternative hypothesis was accepted and null hypothesis was rejected.